Poly(propylene naphthalate-co-propylene 2, 5-furandicarboxylate)s derived from bio-based 2, 5-furandicarboxylic acid (FDCA): Synthesis, characterization and thermo-mechanical properties. (September 2020) - Wang, Guoqiang; Hou, Meichao; Jiang, Min; Wang, Rui; Liang, Yin; Zhou, Guangyuan
Abstract: A series of poly (propylene naphthalate-co-propylene 2, 5-furandicarboxylate)s (PPNFs) were synthesized by the melt polycondensation method from 2, 5-furandicarboxylic acid (FDCA), 2, 6-naphthalenedicarboxylic acid (2, 6-NDCA) and 1, 3-propanediol (1, 3-PDO). Their composition and sequence distribution were analyzed by 1 H NMR and 13 C NMR. Crystallization behaviors, thermal and mechanical properties were investigated. The weight-average molecular weights of PPN, PPF and PPNFs were higher than 28 000 g mol −1 and the polydispersity index was between 2.1 and 2.7. DSC and XRD results show that poly (propylene 2, 5-furandicarboxylate) (PPF) and poly (propylene naphthalate) (PPN) are semi-crystalline polymers, but all PPNFs are amorphous polymers. With increasing the content of FDCA, the initial temperature of α-relaxation rose significantly. When the content of FDCA was 74 mol%, PPNF74 exhibited the high bio-based content (77.6 wt%) and good mechanical properties ( σ m  = 71 MPa and ε b  = 146%). Highlights: A series of 2, 5-furandicarboxylic acid-based copolyesters have been successfully synthesized by the melting polymerization. The effects of composition on microstructure, thermal properties, and mechanical properties were investigated. DMA results show that the initial temperature of α-relaxation rose significantly with increasing the content of FDCA. PPNF74 exhibited the high bio-based content (77.6 wt%) and good mechanical properties ( σ m = 71 MPa and ε b = 146%).